Pengaruh Kepuasan Kerja Dan Komunikasi Terhadap Organizational Behaviour Citizenship (OCB) Di Bank Madina Syariah Yogyakarta - Fadli Akbar; Dyah Pikanthi Diwanti (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background - Job satisfaction, communication and OCB are indicators used to achieve company goals. Bank Madina Syariah is one company that pays close attention to these three things in operating activities in the work environment. Purpose - The purpose of this study was to determine the effect of job satisfaction on the OCB of Bank Madina Syariah in Yogyakarta region, as well as to determine the effect of communication on OCB of Syariah Bank. Design / Methodology / Approach – This type of research is a quantitative study with a questionnaire distribution method using a 4-point Likert scale. The result of this study is that job satisfaction and communication have a positive and significant effect on employee performance of Bank Madina Syariah. Result and Discussion – Simultaneous regression results, obtained the F-count value of 20,570 with probability (p) = 0,000. Based on the provisions of the F test where the probability value (p) ≤ 0.05, Organizational Communication, Job Satisfaction simultaneously affects OCB. Job satisfaction variable obtained t-value of 2,977 regression coefficient (beta) 0.476 with probability (p) = 0.005. Based on the results of data processing where the probability value (p) ≤ 0.05, it can be concluded that Job Satisfaction has a positive and significant effect on OCB. Communication variable with probability (p) = 0.001. The result of the t-value is 3,549, it can be concluded that communication has a positive and significant effect on OCB. Conclusion – Job satisfaction and communication have a significant positive effect on Organizational Behavior Citizenship at Bank Madina Syariah, so that the more satisfaction is established and the better communication runs, the more it can form OCB in the work environment.